cis-acting elements involved in the alternative translation initiation process of human basic fibroblast growth factor mRNA. - Prats, A C (1992)
Four forms of basic fibroblast growth factor (bFGF) are synthesized from the same mRNA, resulting from alternative initiations of translation at three CUG start codons and one AUG start codon. The CUG- and AUG-initiated forms have distinct intracellular localizations and can modify cell phenotypes differently, indicating that control of the alternative expression of the different forms of bFGF has an important impact on the cell. In this study, we investigated the roles of the mRNA 5' untranslated region and the alternatively translated region located between the CUG and AUG codons in the regulation of alternative translation of the different forms of bFGF. Deletions and site-directed mutagenesis were carried out in bFGF mRNA leader, and translation was studied in vitro and in vivo. The results enabled us to identify five cis-acting RNA elements (two in the 5' untranslated region and three in the alternatively translated region) involved in the regulation of either global or alternative initiation of translation. Each of these elements had a specific effect on the level of synthesis of the different forms of bFGF. Furthermore, we showed that the 5' untranslated region regulatory elements had different effects on bFGF translation, depending on the translation system used. These results suggest that bFGF translation is modulated by cis-acting elements corresponding to secondary or tertiary RNA structures, which could be the targets of cell-specific trans-acting factors.